Global–Regional Realignments in Trade, Finance and Development: Introduction to the Special Issue - Susanne Lütz (Global Policy, 2021)
Multilateral Bretton Woods institutions such as the IMF, the World Bank and the WTO are increasingly challenged by a rising number of bilateral, regional and plurilateral organizations. The mandates of global and regional organizations overlap and intersect when trade is being regulated, financial crisis lending is being provided or development is being financed. In this special issue we examine the forms, dynamics and implications of these global–regional realignments for global economic governance. By drawing on the analytical toolbox of regime complexity research, the authors address mechanisms of integration and disintegration in the regime complexes in trade, finance and development from the viewpoint of actors and particularly regional challengers. The papers discuss first, the motives and strategies to spur fragmentation or integration. Second, they examine to what extent actors seek to substitute or complement focal institutions on the global level. Third, the special issue evaluates the implications of a coexistence of integration and disintegration for global economic governance.
Keywords: 320